Financial Literacy and Inclusion Dynamics Within Developing Asian Markets: A Panel Data Assessment Of Indonesia, Malaysia, Singapore, Thailand, Vietnam, Philippines, and India - Faizah Syihab; Hendyansyah Putra; Denta Mandra Pradipta Budiastomo; Nida Aisyah Ramadhani (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study investigates the development of financial literacy and financial inclusion in seven emerging Asian economies, namely Indonesia, Malaysia, Singapore, Thailand, Vietnam, the Philippines, and India during 2015–2025. Using secondary panel data collected from the World Bank Global Findex Database, G20 Financial Inclusion Indicators, and official economic reports, this research analyzes the influence of digital financial access, internet penetration, and GDP per capita on financial literacy performance. The study applies panel regression analysis using a fixed effect model. The findings indicate that digital payment adoption, internet accessibility, and economic growth significantly improve financial literacy levels across Asian developing economies. Singapore and Malaysia demonstrate the highest financial literacy achievements, while Indonesia and the Philippines exhibit substantial improvement during the post-pandemic digital transformation period. This research enriches contemporary literature regarding digital financial inclusion and consumer capacity in emerging territories, offering actionable structural insights for regulatory bodies and financial firms.